Break Time on the School Schedule: Evidence from Basic Education Schools in China - Xu, Xinyuan (Science Insights Education Frontiers, 2023)
The mandatory 10-minute break on the basic education school schedule in China is intended to help students relieve fatigue and pressure and refresh their minds and bodies between lessons. However, instructional activities have often taken precedence over its intended purpose. This article described the current state of break time deprivation among Chinese basic education students and analyzed its causes, with a view to arousing more attention to the protection of the right of the student to rest and leisure activities at school.